Struktur komunitas hama tiga kultivar cabai rawit pada pengaplikasian pestisida nabati - Hesti Kurniahu; Rifa’atul Maulani; Muhammad Rizza Pahlev (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2020)
The utilization of plant-based pesticides and the selection of cultivars of cayenne pepper have not been well optimized by farmers. The purpose of the study was to analyze the types of cayenne pepper pests, examine the association of cayenne pepper cultivars against pest attacks, and analyze the application of plant-based pesticides to pest visits. The research method is experimental with a completely randomized design. The samples of this study are Sret, Mhanu XR, and Cakra Hijau. The research instrument is observation sheets of pest communities before and after the application of plant-based pesticides. The type and number of pests are directly observed and identified in the laboratory. Data on the influence of cayenne pepper cultivar on pest populations were analyzed by ANOVA test while the effect of using plant-based pesticides using t-test. The results showed that pests such as Aphis sp., Polyphagotarsonemus sp., Thrips sp., Bactrocera sp. and Chrysodeixis sp.. Statistical tests showed cayenne pepper cultivar did not influence pest visits while the application of plant-based pesticides had a effect on the decrease in Thrips sp. and Aphis sp.. The conclusion of this study, namely five types of pests attack three cayenne pepper cultivars, the selection of three cayenne pepper cultivars does not affect pest visits, and the application of plant-based pesticides can reduce the number of pest visits Thrips sp. and Aphis sp. significantly.